2017
DOI: 10.1016/j.bpj.2016.11.877
|View full text |Cite
|
Sign up to set email alerts
|

Microcavitation as a Neuronal Damage Mechanism in an In Vitro Model of Blast Traumatic Brain Injury

Abstract: tension)-that this clustering of vesicles is heavily influenced by mechanical tension. Recently, evidence has shown that there is a cortical network of actin, among other things, along the conduit of an axon; its contractility, powered by the acto-myosin machinery, gives rise to the axon's intrinsic tension. Here, we employed transgenic drosophila embryos of stage 16 that have green fluorescence protein tagged to synaptotagmin to track vesicles in neurons. Embryos were dissected such that intact single axons c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 0 publications
1
12
0
Order By: Relevance
“…Under such scenario, the strain rate exerted by the surrounding fluid will be ~10 6 s −1 at 10 μm range and ~10 8 s −1 at 100 nm range. This estimation agrees with the studies focused on possible cavitation damage 15 . From the above equations, we can have a rough idea of how robust the cavitation can be.…”
Section: Introductionsupporting
confidence: 92%
See 1 more Smart Citation
“…Under such scenario, the strain rate exerted by the surrounding fluid will be ~10 6 s −1 at 10 μm range and ~10 8 s −1 at 100 nm range. This estimation agrees with the studies focused on possible cavitation damage 15 . From the above equations, we can have a rough idea of how robust the cavitation can be.…”
Section: Introductionsupporting
confidence: 92%
“…From the above equations, we can have a rough idea of how robust the cavitation can be. Thus, many researchers are now investigating the full mechanism of it during events like traumatic brain injury (TBI) 15 19 . In our previous study 17 , we reported that the cavitation bubble collapse can be strong enough to rupture sub-cellular structure, which has led us here to investigate the vulnerability of microtubule.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, interest has grown in cavitation damage to biological materials including tissue (Mancia et al 2017, Pahk et al 2019) and surgical mesh (Bigelow et al 2019) given its relevance to therapeutic ultrasound and traumatic injuries. Cavitation is a potential source of neuron damage in blast traumatic brain injury (Goeller et al 2012, Estrada et al 2017, Franck 2017), and it has also been proposed as a useful context in which to study tissue damage incurred through high-strain-rate injuries (Estrada et al 2018). Laser surgery (Brujan and Vogel 2006) and therapeutic ultrasound (Brujan 2004) also motivate studies of controlled cavitation damage.…”
Section: Introductionmentioning
confidence: 99%
“…Our study on how biological soft materials respond to rapid mechanical inputs is an important step to understanding possible underlying injury mechanism(s) in blunt trauma and cavitation-induced brain injury. As an example, cavitation is being conjectured as a possible mechanism for mild to moderate traumatic brain injury (mTBI) 46 48 . However, the current understanding of dynamic cavitation in biological materials, e.g., brain tissues, is still very limited and, as a result, a range of mechanical impact that is relevant to cavitation-induced brain injury is still unknown.…”
Section: Conclusion and Discussionmentioning
confidence: 99%